Ventricular Pre-excitation Causing Left Ventricular Dysfunction Partially Reverted After Ablation of the Accessory Pathway - Melo, João Paulo Chaves de; Pavão, Maria Licia Ribeiro Cury; Arfelli, Elerson; Leal, Marcelo Garcia; Marin-Neto, José Antonio; Schmidt, Andre (JOURNAL OF CARDIAC ARRHYTHMIAS, 2020)
Ventricular pre-excitation is one of the rarest causes of cardiomyopathy induced or mediated by arrhythmia. Right accessory pathways, specifically with left bundle branch block pattern, can cause ventricular dysfunction, since abnormal ventricular activation resulting from anterograde atrioventricular conduction can cause atrioventricular, interventricular, and intraventricular dyssynchrony, with asynchronous contraction of the ventricular wall and mitral regurgitation. An asymptomatic patient, with ventricular pre-excitation with left bundle branch block and moderate ventricular dysfunction at echocardiography, was described. The electrophysiological study demonstrated an accessory route of anterior location and with an anterograde refractory period of 600 ms, successfully performing radiofrequency ablation and substantial improvement of ventricular function.